Konsep Metode Pembelajaran dalam Al-Qur’an Surat Ibrahim Ayat 24-25 - Yulianti, Risda; Azis, Abdul; Sahal, Yosef Farhan Dafik (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2019)
The purpose of this study is to find out the interpretation of the Qur'an from the verses of Ibrahim verse 24-25 in the Al-Mishbah interpretation book; as well as to find out the concept of learning methods based on the Qur'an Surah Ibrahim verses 24-25 in the interpretation book Al-Mishbah. The research method used uses a qualitative approach, with descriptive analytic. In collecting data, the authors use the library approach (library research). To obtain research data, the author collects library material, by reading, studying books, newspapers, magazines, and other information materials, especially those related to the concept of learning methods in Q.S Ibrahim verses 24-25. The concept of learning methods contained in the verses of Ibrahim verses 24-25 include the use of the method of parable or amtsal, the method of demonstration, the method of field trips and the method of modeling. So that in learning, the concept of learning methods contained in the verse Ibrahim 24-25 can be used as it should, as learning methods sourced from the Koran.